Souffrance au travail et enjeux de santé : le rôle charnière de l’inflammation et du stress oxydant - Philippe Davezies (Perspectives Interdisciplinaires sur le Travail et la Santé)
Even though the concept of a link between occupational stress and musculoskeletal disorders is generally accepted, the exact nature of the link remains hazy. The information needed to examine the question is scattered across different scientific fields and has only partially been brought together. Nevertheless, the present inquiry emphasizes the echoes and hypothetical or proved links between phenomena such as the emotional repression described by occupational psychopathology, the notion of alexithymia in the field of psychosomatics, the disturbance of cortisol activity and secretion in chronic stress contexts, and the role of inflammation in the genesis of stress-related disorders. The purpose is to show that questions concerning this link can be more fruitfully developed by conducting multidisciplinary investigations.